Determining Company Strategy Priorities at PT X In Efforts to Increase Productivity Performance - Terresa Indrajani Kusuma; Budisantoso Wirjodirdjo (International Journal Labs, 2026)
White crystal sugar is a strategic commodity within Indonesia’s national food security system, with consumption steadily increasing across both household and industrial sectors. However, domestic production has not kept pace with demand, resulting in supply deficits that generate import dependence, price volatility, and structural vulnerability within the sugar industry. Challenges in the downstream sector further hinder national food security. The sugar industry’s supply chain faces persistent inefficiencies in distribution, price instability, trader dominance, and limited logistics infrastructure. A key issue lies in low factory productivity stemming from operational inefficiencies. Government policies, including Minister of Industry Regulation No. 47/2024, require strong stakeholder support, particularly from PT X, a state-owned agroindustry subsidiary. This study identifies strategies for PT X to improve productivity and optimize resource utilization in its sugar factories. Using an integrated Delphi–DEMATEL–ANP approach, the analysis identified seven priority strategies, with two ranking highest in the supermatrix limit, followed by milling process optimization, production–marketing coordination, internal distribution system enhancement, facility layout planning, and machine maintenance and re-layout. Sensitivity tests conducted at weight variations of 5%, 10%, 20%, and 30% confirmed the stability of strategy rankings, demonstrating robustness and systematic consistency. The findings highlight that the most adaptive and applicable productivity improvement strategy for PT X is one that strengthens its overall operational foundation. This approach has the potential to enhance internal efficiency while increasing the company’s contribution to achieving national sugar self-sufficiency.